Case report: Two pediatric cases of long-term leukemia-free survival with relapsed acute T-lymphoblastic leukemia treated with donor CD7 CAR-T cells bridging to haploidentical stem cell transplantation - Song, Yanzhi; Liu, Zhanxiang; Wang, Qi; Gao, Kong; Wu, Tong (Frontiers in Immunology, 2024)
Introduction Patients with relapsed/refractory (r/r) acute T-lymphoblastic leukemia (T-ALL) have a poor prognosis. We developed donor CD7 chimeric antigen receptor T (CAR-T) cells to salvage r/r T-ALL patients and obtained encouraging results. Patients who had not received allogeneic (allo-) hematopoietic stem cell transplantation (HSCT) before CAR-T therapy would develop pancytopenia and immunodeficiency for a long period after CD7 CAR-T therapy; therefore, allo-HSCT is needed in these patients. Here, we report two pediatric r/r T-ALL patients who received donor CD7 CAR-T bridging to allo-HSCT with leukemia-free survival (LFS) and sustained negative minimal residual disease for >2 years. Case presentation Patient 1 was a 10-year-old boy who visited our hospital because of a T-ALL relapse with multiple lymphadenopathies without discomfort. The patient did not achieve remission after one course of induction chemotherapy. The patient then received donor (his father) CD7 CAR-T cells and achieved complete remission (CR). Thirty days after the first CAR-T cell infusion, he received allo-HSCT, and his father was also the donor. His LFS was >3 years. Patient 2 was an 8-year-old boy who was admitted to our hospital with relapsed T-ALL with fever, cough, and mild dyspnea. He did not achieve remission after one course of induction chemotherapy; therefore, he received donor (his father) CD7 CAR-T cells and achieved CR. Twenty-six days after CAR-T cell infusion, the patient received allo-HSCT, with his father as the donor. He has survived for >2 years free of leukemia. At the last follow up, both patients were alive and presented a good quality of life Conclusion The long-term survival of these two patients supports the use of CD7 CAR-T therapy bridging to allo–HSCT as an effective and safe treatment with the capacity to make r/r T-ALL a curable disease, similar to r/r acute B-lymphoblastic leukemia.